Self-Care Behaviors among Patients with Coronary Heart Disease after Percutaneous Coronary Intervention - Rattanaprom, Arunsri; Srisuk, Nittaya; Koson, Naruebeth (Nursing Science Journal of Thailand, 2023)
Purpose: To study self-care behaviors and the association between personal and illness characteristics factors, and self-care behaviors of patients with coronary heart disease after percutaneous coronary intervention. Design: Descriptive research. Methods: The participants were 151 patients with coronary heart disease after percutaneous coronary intervention who came for follow-up at a tertiary hospital in Southern Thailand. Personal data questionnaire, records of illness characteristics, and self-care behavior questionnaire for patients with coronary heart disease were used. Data were analyzed using descriptive statistics and chi-square test for the association Main findings: The participants had inadequate self-care behavior scores (a score <70) for all three aspects: self-care maintenance (64.29±12.10), self-care monitoring (64.00±18.40), and self-care management (63.23±19.28). It was found that personal factors including age, educational level, and a caregiver at home were associated with self-care maintenance ( 2 = 27.07, 9.73, 5.63, respectively, and ps < .05) and self-care management ( 2 = 19.33, 12.05, 15.24, respectively, and ps < .05). The illness characteristics factors showed that the left ventricular ejection fraction, chest pain severity, severity of comorbidity, and duration of treatment were significantly associated with self-care maintenance ( 2 = 4.71, 24.65, 6.24, 6.12, respectively and ps < .05). Illness characteristics factors that were significantly associated with self-care monitoring included chest pain severity and duration of treatment ( 2 = 8.72, p < .05 and 2 = 9.43, p < .05, respectively). None of the illness characteristics factors was associated with self-care management. Conclusion and recommendations: Patients with coronary heart disease after angioplasty did not have sufficient self-care behavior. Personal and illness factors associated with the self-care behavior included age, educational level, caregiver at home, left ventricular ejection fraction, chest pain severity, severity of comorbidity, and duration of treatment. Nurses should develop a program to enhance the patients’ self-care behavior. Assessment of the associated factors should be given the importance so that the program activities would be tailored to suit with the personal and illness characteristics of the patients resulting in effectiveness of the program.